2000
DOI: 10.1161/01.cir.102.3.278
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Abnormal Electrocardiographic Patterns in Trained Athletes

Abstract: Background-The prevalence, clinical significance, and determinants of abnormal ECG patterns in trained athletes remain largely unresolved. Methods and Results-We compared ECG patterns with cardiac morphology (as assessed by echocardiography) in 1005 consecutive athletes (aged 24Ϯ6 years; 75% male) who were participating in 38 sporting disciplines. ECG patterns were distinctly abnormal in 145 athletes (14%), mildly abnormal in 257 (26%), and normal or with minor alterations in 603 (60%). Structural cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
326
11
46

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 491 publications
(410 citation statements)
references
References 39 publications
27
326
11
46
Order By: Relevance
“…13 The abnormal frequency we noted is also considerably higher than the 45% prevalence reported in a large sample of athletes in various sports that did not include American football players. 7 Since our data are descriptive, we cannot confirm that our abnormal ECG findings are caused by football participation, nor can we predict that sport termination would resolve them. However, the magnitude of the abnormal frequency (79%), coupled with the results of other studies in athletes, 2,4,7 supports the speculation that football participation is a contributing causal factor.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…13 The abnormal frequency we noted is also considerably higher than the 45% prevalence reported in a large sample of athletes in various sports that did not include American football players. 7 Since our data are descriptive, we cannot confirm that our abnormal ECG findings are caused by football participation, nor can we predict that sport termination would resolve them. However, the magnitude of the abnormal frequency (79%), coupled with the results of other studies in athletes, 2,4,7 supports the speculation that football participation is a contributing causal factor.…”
Section: Discussionmentioning
confidence: 72%
“…7 Since our data are descriptive, we cannot confirm that our abnormal ECG findings are caused by football participation, nor can we predict that sport termination would resolve them. However, the magnitude of the abnormal frequency (79%), coupled with the results of other studies in athletes, 2,4,7 supports the speculation that football participation is a contributing causal factor. Others have reported that the cardiac changes in athletes that accompany training are generally benign and are reversible when training ceases.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations